Analisis Biaya Dan Pendapatan Lebah Madu Must Yoan Farm Kelurahan Kalampangan Kalimantan Tengah: The Analysis Of Cost And Income For Honey Bees Must Yoan Farm Kalampangan Village Central Kalimantan - Pije Marlomak Simbolon; Sari Mayawati; Nuwa Nuwa (HUTAN TROPIKA, 2022)
The Analysis of Cost and Income Must Yoan Farm Honey Bees, Kalampangan Village, Central Kalimantan. Honey bee cultivation in Central Kalimantan, especially the city of Palangka Raya, has the potential to be developed, considering the natural resources are very supportive and meet various location requirements for honey bee cultivation, in addition, especially honey bee farmers in the Kalampangan village have started this business, but stopped in mid this is due to a lack of information in terms of analyzing costs and income in this business, many think they will experience losses in this honey bee business while honey bees are a very good business because all of honey bees can produce economic resources starting from bees to waste and in the village of Kalampangan, the majority of people cultivate crops, so it is very good for natural pollination assisted by honey bees. Therefore, a proper analysis of the business being carried out is needed to find out the problems that occur at the research site and the solutions that will be taken. The method used consists of: 1. calculating fixed costs and income 2. Calculating honey bee business profits 3. Calculating break even point (BEP). 4. Calculating the feasibility of a honey bee business. The results of the study, 1. The cost of Rp. 355.400.000, and the amount of income is Rp.901.090.000, 2. Profit earned is Rp.545.690.000, 3. BEP (Break Even Point) in rupiah is Rp.231,806,626 and BEP unit is 1,825.71 4 The level of business feasibility, the value of the B/C Ratio is 2.54